Tinjauan Dampak Pernikahan Dini dari Berbagai Aspek - Dini Fadilah (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2021)
Marriage is a sacred activity carried out to unite men and women in legal ties of the household in the eyes of religion and state. Marriage should be carried out by a man and woman who are of legal age and are vulnerable to the age of 19 years and over. However, the tradition of early marriage or marriage under the age of 19 is a common practice in Indonesian society and is even more prevalent. Early marriage is not something that is allowed considering the many negative impacts it has, starting from physical, mental, social and other health. The purpose of conducting this research and making this article is so that readers can understand and know the impact of this early marriage. Thus, it is hoped that the Indonesian people will be able to filter knowledge and news about early marriage, so that early marriage does not become a justifiable scourge anymore. The method used in this research is a qualitative method with a descriptive analysis approach assisted by various sources with clear facts. In fact, from the results of research through surveys filled in by several people, many early marriages occur in their environment due to several factors, one of which is pregnancy out of wedlock. With this early marriage, it can be categorized as a problem that could destroy the future of the Indonesian nation.